Ligand exchange processes on solvated beryllium cations v. Water exchange on [Be(X)(H2O)3]+ (X: H-,F -, Cl-, Br-, OH-, CN-, NCNCN-) - Walther, Markus; Puchta, Ralph; van Eldik, Rudi; et al. (Zeitschrift für Anorganische und Allgemeine Chemie, 2011)
The water exchange reaction of BeII complexes in the series [Be(X)(H2O)3]+ (X = H-, F -, Cl-, Br-, OH-, CN-, NCNCN-) was studied by DFT calculations (RB3LYP/6-311+G **) and identified as an associative interchange mechanism. The influence of X on the activation energies was examined and found to be largely negligible, thus making them all act as spectator ligands. The energies for addition of a fourth water molecule, representing the second coordination sphere, were approximately half of that found for similar dicationic complexes and close to that found for monocationic species like [Li(H2O) 4]+. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Beryllium; Density functional calculations; Halogens; Hydration; Water exchange